Follow-up of Nonarteritic Anterior Ischemic Optic Neuropathy With Optical Coherence Tomography Angiography. Issue 4 (December 2021) - Aghsaei Fard, Masoud; Ghahvechian, Hossein; Subramanian, Prem S.
Abstract : Background: Peripapillary and macular microvasculature alterations after nonarteritic ischemic optic neuropathy (NAION) have been investigated in several studies. We aimed to explore the vascular changes from acute NAION (aNAION) to chronic NAION (cNAION). Methods: This prospective observational study composed of 16 eyes with aNAION and 40 healthy age-matched controls. Eyes with NAION were followed up for more than 6 months after acute event. Optical coherence tomography angiography (OCTA) was used to evaluate peripapillary and macular vessel densities (VDs). The customized software was used for calculating deep retinal VD to attenuate the large superficial vessel projection effect. Result: The mean age of patients with NAION and controls was 56.13 ± 13.2 and 54.46 ± 15.5 years, respectively ( P = 0.195). Radial peripapillary capillary density was significantly lower in both eyes with aNAION and eyes with cNAION than healthy eyes. Peripapillary capillary density decreased significantly from the acute to the chronic phase of NAION with values of 41.77 ± 4.05% and 34.35 ± 7.30%, respectively ( P < 0.001). The mean superficial macular VD was 46.83 ± 3.47% in aNAION and 44.49 ± 4.50% in cNAION eyes with no significant difference between them ( P = 0.252), but both were lower than control eyes. Deep macular VD was not affected in aNAION and cNAION eyes compared with control eyes. Correlation analysis in eyes with cNAION revealed that there were significant correlations between peripapillary nerve fiber layer and the capillary density (r = 0.772, P < 0.001) and between ganglion cell complex thickness and corresponding superficial macular VD. Conclusions: Although a decrease in peripapillary capillary density in aNAION eyes with active disc edema progressed when evaluated in the cNAION state, progressive VD loss was not observed in the macular area, suggesting a nonprogressive nature of macular vessel involvement in NAION.